Prevalence of bronchiectasis in inflammatory bowel disease: a systematic review and meta-analysis - Ma, Yu; Qiang, Zhihui; Zhou, Miaomiao; Zhang, Tianyi; Li, Zhuoyang; Zhong, Haicheng; Chang, Yue; Ning, Zimeng; Liu, Yun (Frontiers in Medicine, 2024)
Objective The aim of this study was to conduct a systematic review and meta-analysis of the incidence of inflammatory bowel disease-associated bronchiectasis (IBD-BE) and to explore the possible risk factors for IBD-BE, which could help to understand the pulmonary involvement in patients with IBD and to determine the global incidence of the disease. Methods We searched PubMed and EMBASE databases to identify information on the prevalence of IBD-BE among IBD patients in the published literature. Information was extracted on study design, country, year, IBD-BE testing method, IBD characteristics, number of IBD-BE cases and total number of IBD patients, and factors associated with IBD-BE. We conducted meta-analyses using random-effects or fixed-effects models to estimate the prevalence of IBD-BE among IBD patients. Results Out of a total of 682 studies, we identified 16 studies that reported prevalence. These studies used a heterogeneous approach to identify IBD-BE. In these 16 studies, there were 92,191 patients with IBD, of whom 372 cases of IBD-BE were identified. The results of the meta-analysis showed that the overall prevalence of IBD-BE in IBD derived from the use of a random effects model was 5.0% (95% CI 2.0–12.0%). In contrast, the prevalence of IBD-BE in studies using high-resolution chest computed tomography (HRCT) imaging was 12% (95% CI 4–39%) using a random-effects model. When only retrospective studies with sample sizes greater than 100 (n = 6) were considered, the prevalence was 1% (95% CI 0–1%). However, when only retrospective studies with sample sizes less than 100 were included (n = 4), the prevalence was 29% (95% CI 6–100%); in prospective studies (n = 6), the combined prevalence was 11% (95% CI 4–29%). we performed a subgroup analysis of the differences in the incidence of IBD-BE between the different studies, each of which we subgrouped by type of study, type of disease, duration of disease, and diagnostic modality, and the results showed no significance. Future studies should standardize methods to identify IBD-BE cases and investigate the natural history and clinical course given the relatively high prevalence among IBD. Conclusion In this systematic review and meta-analysis, the prevalence of IBD-BE was 12% among studies with HRCT imaging, suggesting that bronchiectasis may be an underestimated common extraintestinal manifestation of IBD. Asymptomatic patients with IBD-BE may present with abnormalities on HRCT or pulmonary function tests. Future studies should standardize methods to identify IBD-BE cases and investigate the natural history and clinical course given the relatively high prevalence among IBD.